2002
DOI: 10.1002/1521-3951(200212)234:3<897::aid-pssb897>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Electromechanical Coupling Coefficient for Surface Acoustic Waves in GaN-on-Sapphire

Abstract: The electromechanical coupling coefficient for surface acoustic waves propagating in GaN-on-sapphire structure has been evaluated using in situ measurements of the SAW attenuation during the evaporation of a metal film on the GaN surface. The extracted values for samples with GaN layer thicknesses of 2.2-2.4 mm were in the range of 0.06-0.09% at SAW frequencies of 200-300 MHz.Introduction Surface acoustic waves (SAWs) have found important applications in material research, signal processing, and telecommunicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 9 publications
(11 reference statements)
1
11
0
Order By: Relevance
“…[6][7][8][9][10][11][12][13] In these studies, the thickness and the resistivity of the GaN films were assumed to be key factors to affect the surface acoustic modes and the electromechanical coupling coefficients. 9,10,[14][15][16] The emergence of various acoustic modes is dependent on the ratio between the GaN film thickness and the SAW wavelength. 6,8 The electromechanical coupling coefficient of GaN layers with different thickness and different resistivities were reported in a large range from 0.015% to 4.3%, and it was pointed out that the high resistivity of GaN layer might be preferable for improving the performances of SAW devices.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[6][7][8][9][10][11][12][13] In these studies, the thickness and the resistivity of the GaN films were assumed to be key factors to affect the surface acoustic modes and the electromechanical coupling coefficients. 9,10,[14][15][16] The emergence of various acoustic modes is dependent on the ratio between the GaN film thickness and the SAW wavelength. 6,8 The electromechanical coupling coefficient of GaN layers with different thickness and different resistivities were reported in a large range from 0.015% to 4.3%, and it was pointed out that the high resistivity of GaN layer might be preferable for improving the performances of SAW devices.…”
mentioning
confidence: 99%
“…In this work, Fe-doped GaN epitaxial films with wurtzite structure were grown on (0001) sapphire substrate, and the crystal orientation GaN is parallel to sapphire [11][12][13][14][15][16][17][18][19][20]. Two Fe-doped GaN samples of different thickness were employed in our experiment, and their thickness are respectively 33 lm (sample 1) and 15lm (sample 2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Focusing on the high piezoelectricity, several authors have investigated transversal filters fabricated on ͑Al͒GaN layers on sapphire [4][5][6][7][8][9][10] or SiC 11 substrates, and discussed fundamental properties of surface acoustic wave ͑SAW͒ in these systems, such as dispersion of SAW velocity, 5,7,9,11 temperature coefficient of frequency, 6,7,10 and effective electromechanical coupling constant K eff 2 . 4,6,8 It has been reported that the device characteristics of GaN-based transversal filters are sensitive to ultraviolet illumination. 12,13 Recently, Grajal et al 14 showed that the insertion loss of transversal filters fabricated on AlGaN/ GaN heterostructures changes when dc bias voltages are applied to their interdigital transducers ͑IDTs͒.…”
mentioning
confidence: 99%
“…D UE to their excellent electrical and thermal properties as well as marked piezoelectricity [1], group-III nitrides have been widely applied to not only high-frequency highpower electron devices [2], [3] but also surface acoustic wave (SAW) devices: The fundamental properties of SAWs in (Al)GaN layers-such as the electromechanical coupling coefficient [4], [5], dispersion of the SAW velocity [6]- [8], response to ultraviolet illumination [9], and interaction between photogenerated carriers and SAWs [10]-were investigated. The present authors previously discussed the characteristics of SAW devices fabricated on GaN layers exposed by dry etching [11], side-gate effects [12], and excitation of SAWs using n + -GaN-based interdigital transducers (IDTs) [13].…”
Section: Saw Filters Composed Of Interdigital Schottky and Ohmic Contmentioning
confidence: 99%